Quality of soybean seeds cultivar RR 8473 RFS stored in refrigerated and non-refrigerated environments - Lander, Marcio Ens; Menezes Filho, Antonio Carlos Pereira de; Côrrea, Fernando Rezende; Batista-Ventura, Hellen Regina Fernandes; Ventura, Matheus Vinicius Abadia (Brazilian Journal of Science, 2022)
During the post-harvest period, seeds are susceptible to several factors that can reduce physiological potential and vigor. The rate of seed deterioration is influenced by genetic factors, management methods and storage conditions. The experiment was carried out at the SPU (Seed Processing Unit) at Fazenda São Francisco, in the municipality of Rio Verde, Goiás, Brazil. The treatments consisted of seed harvesting in: 1 - post-precipitation, stored in an acclimatized environment; 2 - post-precipitation, stored in a non-air-conditioned environment; 3 - pre-precipitation, stored in an air-conditioned environment; 4 - pre-precipitation, stored in a non-air-conditioned environment. Tests were carried out to assess the quality, starting with the quality assessment right after the harvest, bimonthly according to the standard tests for quality verification until the date of a possible planting in field conditions (harvest 21/22) (AR (emergence in sand), TZ (tetrazolium), EA 72h (accelerated aging 72 h), EA 48 h (accelerated aging 48 h), EA 24 h (accelerated aging 24 h) and ES (Emergence in soil bed). seeds harvested before or after precipitation and stored in a climate-controlled environment showed greater vigor and viability.